Cultural Diversity Analysis of Visual Content in the Indonesian Textbook: My Next Words for Elementary School Grade 1 - Febriana, Ridha Alya; Husaini, Nurfadillah; Rohim, Abdul (JEdu: Journal of English Education, 2024)
The aim of this research is to analyze visual content that elevates Indonesian culture from the book "My Next Words For Elementary School Grade 1" published by Lala Intan Gemala et al. from the Ministry of Education and Culture. This research is using descriptive qualitative method and Roland Barthes' semiotic theory: The science of interpreting a signal, where language is also a structure of signals with a particular message from society. According to this study, the visual content of the book contains several categories of cultural diversity values. In the first image, the girl is portrayed as emphasizing the importance of helping parents, which is categorized as "Respecting Other People's Traditions" (ROPT). In the second image, two female students are depicted wearing different-shaped uniforms, demonstrating "Appreciating Womens Equal Rights" (AWER). In "Appreciating Other People's Cultural Products" (AOPCP), this is demonstrated in one of the traditional Indonesian costumes that the teacher was wearing, depicted in the third image. The result proved that the three photos do not reflect Indonesia's entire cultural prosperity.